Music, Value and the Passions - Ridley, Aaron (Cornell University Press, 2019)
For a century there has been a divergence between what music theorists say music is about and what the ordinary listener actually experiences. Music theory has insisted on a separation of musical experience from the experience of emotions, from the passions. Yet a passionate experience of music is just what most ordinary listeners have. Charting a new course through the minefield of contemporary philosophy of music, Aaron Ridley provides a coherent defense of the ordinary listener's beliefs. Focusing on instrumental music in the classical Western canon, Ridley defends the commonsense position on music and attempts to return the experience of music to the ordinary listener. He argues that, through a sympathetic experience of certain musical gestures, the listener is able to grasp the passions of which the music is expressive. If the passions are properly understood, he contends, there is a place for passion in a philosophical understanding of music. Similarly, the expression of passion may properly be considered part of the value of the music we hear.